Anxiety, Depression and Quality of Life Among Parents Attending School Counseling Programs: Are they Effected by Sociodemographic Characteristics? - Theofilou, Paraskevi; Tafarli, Georgia (Current Psychiatry Research and Reviews, 2024)
Parental stress and depression are factors that significantly affect the exercise of the parental role and have an impact on the upbringing of children and their quality of life. The purpose of this study is to investigate the differences between the dependent variables of quality of life, anxiety and depression in relation to the demographic characteristics, as an independent variable, in the entire sample before the implementation of parent counseling. A sample of 160 parents was collected to participate. The psychometric tools have been used are: The Spielberger Stress Trait Anxiety Inventory (STAI), the Beck depression Inventory (BDI), and the Health and well-being Questionnaire (The RAND 36-Item Healthy Survey, SF-36, Version 1.0). It was found that men have better quality of life in both physical and emotional health, lower anxiety and depression. A positive correlation between age and emotional health was found. Younger parents have more anxiety, depression and generally poorer emotional health than older parents.
Keywords: Anxiety